Metabolomic profile of swimming sessions performed at different exercise intensities in high performance swimmers - Govus, A.; Lawler, N. G.; Mitchell, L. J. G.; Goldsmith, C.; Kozlovskaia, M.; Pyne, D. B. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Metabolic phenotyping uses mass spectrometry to comprehensively profile hundreds to thousands of metabolites (the products of metabolism) in a small blood volume (~0.02-0.10 mL). Such information can provide a detailed overview of the metabolic responses to swimming sessions performed at difference exercise intensities. This study explored the metabolic responses associated with three swimming sessions performed in the moderate, heavy, and severe exercise intensity domains in high performance male and female swimmers. METHODS: Sixteen (9 males, 7 females, age: 16-24 years) Tier 3 swimmers performed a 12 × 25 m step test to determine their critical swimming speed. One week later, swimmers undertook three swimming sessions performed in the moderate (5 × 400 m on 6` at A1/A2 speed), heavy [3 × (8 × 100m on 1` 40 holding critical speed, 100 m recovery on 2`)], and severe exercise intensity domains [3 × (1 × 35 m dive max on 2`, 2 × 50 m dive max on 3`, 200 m recovery on 5`]. Each session was scheduled two days apart. 1.0 mL capillary whole blood samples were collected before and immediately following the cool down for each session, centrifuged and 0.1 mL of blood plasma was frozen for metabolic phenotyping using 1H-NMR and LC-MS spectrometry to give broad lipoprotein, lipidomic and amino acid coverage. RESULTS: Preliminary random forest classification analysis of pre- vs. post-exercise time points revealed that exercise in the severe domain altered metabolites involved in membrane structure and energy metabolism (triacylglycerol`s and phosphatidylethanolamine`s), whereas exercise in the heavy and moderate domain mainly altered free fatty acids involved in oxidative energy metabolism and the inflammatory response (e.g., eicosatrienoic acid). Analysis of the log2fold change of post/pre-exercise values between swimming sessions distinguished different fatty acid profiles involved in cell membrane structure and the inflammatory response between sessions performed in the moderate, heavy, and severe domains, respectively. However, the metabolomic profile of the swimming sessions performed in the moderate and heavy domains could not be discriminated from each other as they showed a similar metabolic response. CONCLUSION: Similar metabolic responses (altered fatty acid metabolism) were observed in the swimming sessions performed within the moderate and heavy domains, but changes in metabolites involved in cell membrane structure and the inflammatory response were key features of exercise performed in the severe intensity domain. Further research is needed to understand the variability and long-term metabolomic responses to routine swimming training in high performance swimmers.